﻿The inhibitory activity of Cassia alata leaves extract on denv-2 replication infected mice - Marissa Angelina; Muhammad Hanafi; Tri Yuliani; Franciscus Suyatna; Tjahjani Mirawati Soediro; Beti Ernawati Dewi (Pensoft Publishers, 2022)
Dengue fever is widely prevalent in Indonesia and many other tropical countries. There has been no antiviral protection against DENV (dengue virus) due to the scarcity of animal models that replicate the symptoms of its infection in humans. Subsequently, Balb/c mice were used to optimize the animal models that were infected with DENV, and measurements of DENV titer, platelet count and leukocytes counts were taken after six days of CA (Cassia alata leaves extract) treatment to examine the inhibitory activity of viral replication on dengue-infected mice. The results showed that CA significantly reduced DENV titer and increased platelet count compared to the control group (P < 0.05) but had no significant effect on leukocyte counts (P > 0.05). Therefore, it could be implied that Cassia alata could be further investigated for medication against DENV, prospectively.